2009
DOI: 10.1161/circulationaha.109.863241
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry, Body Fat, and Venous Thromboembolism

Abstract: Background-Obesity, measured as body mass index, is associated with venous thromboembolism (VTE). Body mass index is a marker of excess weight and correlates well with body fat content in adults; however, it fails to consider the distribution of body fat. We assessed the association between anthropometric variables and VTE. Methods and Results-From 1993 to 1997, 27 178 men and 29 876 women 50 to 64 years of age were recruited into a Danish prospective study (Diet, Cancer, and Health). During 10 years of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 23 publications
10
93
1
1
Order By: Relevance
“…Indeed Choy et al, 28 showed an association between increased WC and raised blood pressure. Although several studies have shown that a larger HC is protective against HT and metabolic diseases 29,30 , our study showed such protection in males only while larger HC was associated with higher blood pressure in females. Some of these studies which showed that a large HC confers protection against CVDs also demonstrated that without controlling for BMI or WC, HC was associated with higher blood pressure in females 33,34 .…”
contrasting
confidence: 90%
“…Indeed Choy et al, 28 showed an association between increased WC and raised blood pressure. Although several studies have shown that a larger HC is protective against HT and metabolic diseases 29,30 , our study showed such protection in males only while larger HC was associated with higher blood pressure in females. Some of these studies which showed that a large HC confers protection against CVDs also demonstrated that without controlling for BMI or WC, HC was associated with higher blood pressure in females 33,34 .…”
contrasting
confidence: 90%
“…Our study was confined to women, but other prospective studies have found a similar relationship between increasing body size and venous thromboembolism risk for men in the absence of surgery, 28,30,31,49,50 as have studies in which sex-adjusted estimates were reported. 51,52 Previous studies that explored the independent effects of obesity on venous thromboembolism risk following surgery have not reported sex-specific analyses, 8 -15 so it is not known whether the relationship differs between women and men.…”
Section: Strengths and Limitationssupporting
confidence: 64%
“…[27][28][29][30][31] Overall, previous prospective studies have reported a 2-to 3-fold increased risk of venous thromboembolism associated with a body mass index Ն30 kg/m 2 in comparison with women who were not overweight or obese. [27][28][29][30][31][32][33] These studies included far fewer participants and cases of venous thromboembolism than this study and consequently their power to undertake detailed explorations of risk was limited; the study with the largest number of cases, the Iowa Women's Health Study, 29 included only 463 events that did not occur after surgery, a recent cancer diagnosis, or another acute precipitating event (compared with Ͼ4000 events included here).…”
Section: Findings In Relation To Previous Studiesmentioning
confidence: 93%
“…Our inability to establish a statistically significant impact of smoking on the risk of VTE may be attributable to the fact that information regarding smoking was available on only 65% of the cohort. The consistent risks of smoking for VTE in the general population were established by studies with much larger sample sizes (4000 to 1.1 million individuals) (38)(39)(40)(41)(42)(43). Likewise, the lack of a protective association between antiplatelet or HMG-CoA reductase inhibitor use and VTE risk may relate to the sample size.…”
Section: Discussionmentioning
confidence: 97%